Mechanical design of a lower limb exoskeletonfor rehabilitation of paraplegic patients - Marafa, Nasiru Adamu (2021)
Dissertação (mestrado) — Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Mecânica, 2021.